Effect of Urea Fertilizer and Harvest Time on Growth and Production Quality of Sweet Corn (Zea mays saccharata) - Tri Rini Kusparwanti; Muhammad Zayin Sukri; Hendra Basirun Sinaga (SINTA Journal (Science, Technology, and Agricultural), 2022)
This study examines the use of Urea Fertilizer on sweet corn plants and harvest time in an effort to increase production and quality. This study sought to identify the effect of giving various doses of urea fertilizer with harvest time and it was found that the interaction of fertilizer treatment with harvest time had a significantly different effect on sweet corn production. The study was conducted using a factorial randomized block design (RAK) with two factors, namely urea dose (P) consisting of 3 levels and harvest time (B) with 3 levels and 3 replications, so that there were 27 experimental units. Each experimental unit was taken 8 experimental samples. The data were analyzed using analysis of variance and continued with the 5% DMRT test. The treatment was given: P1 = Urea at a dose of 300 kg/ha P2 = Urea at a dose of 225 kg/ha P3 = Urea at a dose of 150 kg/ha and B1 = 12.00 WIB, B2 = 14.00 WIB, B3 = 16.00 WIB. The parameters studied were plant height (cm); Number of leaves (strands); Cob length (cm); Cob diameter (cm); and the level of sweetness (brix) and weight of cobs per bed. The implication that can be drawn from the results of this study is that the growth of sweet corn (plant height, number of leaves) and production (cob length, cob diameter, cob weight per sample, sweetness level) were not significantly different, the interaction of urea fertilizer treatment 150 kg/ha with a harvest time of 14.00 gave a significantly different effect on the weight of cobs per bed.